Application of An Agroecological Approach to Dryland Sustainable Food House Systems to Increase Productivity and Environmental Sustainability: A Literature Review - Pramesthi, Ardi Yoga; Susilowati, Lolita Endang; Suwardji, Suwardji; Mulyati, Mulyati (Jurnal Biologi Tropis, 2025)
Altieri, M. A. (2018). Agroecology: the science of sustainable agriculture. CrC press. Bader, C. L., Moeller, N. I., Grard, B., Wezel, A., Féret, S., Andreotti, F., & Vandenbroucke, P. (2026). Philanthropic Funding for Agroecology in Europe–Opening the (black) box of sustainable food system actors. Agroecology and Sustainable Food Systems, 50(1), 164-193. https://doi.org/10.1080/21683565.2025.2489416 Bahua, M. I., Musa, N., & Irsan, L. M. (2024). Pengelolaan rumah pangan lestari dalam pencegahan stunting pada rumah tangga petani. Jurnal Abditani, 7(2), 143-149. https://doi.org/10.31970/abditani.v7i2.372 Bedmutha, K. (2025). Organic Farming and Its Environmental Benefits: A Comprehensive Review. British Journal of Agroecology and Environmental Studies, 2(1), 16-24.  https://doi.org/10.61424/bjaes.v2i1.432 BKP. (2018). Pekarangan Pangan Lestari (P2L). Badan Pangan Nasional. https://badanpangan.go.id/blog/post/kawasan-rumah-pangan-lestari. Darsono, W., Putri, E. I. K., & Nahrowi, N. (2016). Prioritas Wilayah Pengembangan Ternak Ruminansia di Kabupaten Tasikmalaya The Priority Region of Ruminant Development in Tasikmalaya District. Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 4(3), 356-363. 10.29244/jipthp.4.3.356-363 Dutta, B., Goswami, A., Medhi, B. K., & Deka, K. (2024). Soil Health and Plant Nutrition for Sustainable Agriculture. In Role of Agronomy in Cultivating a Sustainable Food Future (pp. 19-28). Cornous Publications LLP. 10.37446/edibook092024/19-28. Fitri, M. A., & Usni, M. (2024, October). Systematic Literature Review: Pertanian Berbasis Agroekologi Untuk Mendukung Pertanian Berkelanjutan. In Prosiding Seminar Nasional Pembangunan Dan Pendidikan Vokasi Pertanian (Vol. 5, No. 1, pp. 427-436). https://doi.org/10.47687/snppvp.v5i1.1125 Gupta, S. (2025). A Review on the Role of Agroecology in Achieving Sustainable Development Goals. British Journal of Agroecology and Environmental Studies, 2(1), 38-48.  https://doi.org/10.61424/bjaes.v2i1.433 Harto, YB. (2019). Indigofera, Pakan Ternak Berkualitas Tinggi. Jagad Tani Edisi Oktober 2025. Hidayat, M. (2023). Peran Petani Milenial terhadap Transformasi Pertanian di Indonesia. Journal Reseacrh Gate. 1(1): 1-6. file:///C:/Users/limlo/Downloads/PeranPetaniMilenialTerhadapTransformasiPertaniandiIndonesia.pdf JD09. (2023). Pekarangan Pangan Lestari RW 03 Cilangkap Bakal Panen Perdana Pekan Depan. Berita Depok. https://berita.depok.go.id/pekarangan-pangan-lestari.   Kamara, A. Y., Omoigui, L. O., Kamai, N., Ewansiha, S. U., & Ajeigbe, H. A. (2018). Improving cultivation of cowpea in West Africa. Achieving Sustainable Cultivation of Grain Legumes, Burleigh Dodds Science Publishing Limited, Volume 2, 235-252. https://doi.org/10.19103/AS.2017.0023.30 Kerr, R. B., Postigo, J. C., Smith, P., Cowie, A., Singh, P. K., Rivera-Ferre, M., ... & Neufeldt, H. (2023). Agroecology as a transformative approach to tackle climatic, food, and ecosystemic crises. Current Opinion in Environmental Sustainability, 62, 101275. 10.1016/j. cosust.2023.101275. Lestari, D. (2020). Siklus Nitrogen Beserta Penjelasannya. Siswapedia. https://www.siswapedia.com/siklus-nitrogen-beserta-penjelasannya.  Mauverne, R. and Conches, CD., 2008. Agricultural Ecosystems, Fact and Trends. World Business Council Sustainable Development - IUCN. Novanda, RR., Muflihani AR., Priyono BS., Nabiru M., Irnad, Apriani R., Ulma RO., & Defliyanto. (2024). Pekarangan dengan Prinsip Kawasan Rumah Pangan Lestari di Desa Pantai Indah Pulau Baai Kota Bengkulu. Dharma rafflesia : Jurnal Ilmiah Pengembangan Dan Penerapan IPTEKS. 22(1), 27–39.https://doi.org/10.33369/dr.v22i1.34333 Puspitasari, Y., Suriyanti, S., & Nontji, M. (2022). Lama fermentasi dan volume effective microorganism-4 (EM4) dalam pembuatan pupuk organik padat berbahan dasar serbuk gergaji kayu dan kotoran ayam. AGrotekMAS Jurnal Indonesia: Jurnal Ilmu Peranian, 3(2), 124-135. https://doi.org/10.33096/agrotekmas.v3i2.254 Ririn. (2012). Pemanfaatan Lahan Pekarangan di Kelompok Wanita Desa Mirigambar Dusun Miridudo Kecamatan Sumbergempol. BPS Sumbergempol, Tulungagung, Jawa Timur. https://bppsumbergempol.blogspot.com.  Silici, L. (2014). Agroecology: What it is and what it has to offer. Issue Paper 14629IIED. London: International Institute for Environment and Development. https://oer.uinsyahada.ac.id/files/original/864701ec4ff28c5e46a3b1e398a5b2bd.pdf Soeharsono. (2008). Bionomika Ternak. Bandung (ID): Widya Padjadjaran. Somashekar, K. S., Abhishek, G. J., Kumar, V., Tiwari, A., Lakra, T. S., & Chauhan, B. (2024). Agroecology principles, practices and their impact on sustainable food systems. European Journal of Nutrition & Food Safety, 16(9), 249-260. 10.9734/ejnfs/2024/v16i91544. Susanti, W. I., Cholidah, S. N., & Agus, F. (2024). Agroecological nutrient management strategy for attaining sustainable rice self-sufficiency in indonesia. Sustainability, 16(2), 845. https://doi.org/10.3390/su16020845. Tampubolon, B., Harjanti, D. T., Adlika, N. M., & Christanto, L. M. H. (2020). Pemanfaatan lahan gambut menjadi lahan potensial untuk menjaga ketahanan pangan di Kalimantan Barat. Geodika: Jurnal Kajian Ilmu dan Pendidikan Geografi, 4(2), 182-191. https://e-journal.hamzanwadi.ac.id/index.php/gdk/article/view/2765 Titisari, PW. (2024). Dasar – Dasar Ekologi Pertanian. Cetakan 1. Penerbit Uir Press. Tomich, T. P., Brodt, S., Ferris, H., Galt, R., Horwath, W. R., Kebreab, E., ... & Yang, L. (2011). Agroecology: A review from a global-change perspective. Annual Review of Environment and Resources, 36(1), 193-222. 10.1146/ annurev-environ-012110-121302. Uddin, M. B., & Antriyandarti, E. (2025). Strategies to overcome the declining trend of young farmers: A comprehensive review of agricultural development issues. Journal of Agrosociology and Sustainability, 3(1), 1-18. https://doi.org/10.61511/jassu.v3i1.2025.1820.  Vikas, & Ranjan, R. (2024). Agroecological approaches to sustainable development. Frontiers in Sustainable Food Systems, 8, 1405409.  10.3389/fsufs.2024.1405409.  Wezel, A., Bellon, S., Doré, T., Francis, C., Vallod, D., & David, C. (2009). Agroecology as a science, a movement and a practice. A review. Agronomy for sustainable development, 29(4), 503-515. 10.1007/978-94-007-0394-0_3      Wihardjaka, A. (2018). Penerapan model pertanian ramah lingkungan sebagai jaminan perbaikan kuantitas dan kualitas hasil tanaman pangan. Jurnal pangan, 27(2), 155-164.    https://doi.org/10.33964/jp.v27i2.376